Art, body and politics in the 1980s: disobedient aesthetics in the under scene of Buenos Aires - Lucena, Daniela (2015)
Our research fits within a perspective of study which, in recent times, has proliferated in several investigations concerning to the symbolic production during the last military dictatorship in Argentina. It´s a perspective that, rather than focus on the paralyzing effects of the disappearing power that molded a docile and terrified social body, held the look in the actions and the strategies ? of fugue, of confrontation, of strength, of disobedience - deployed by some cultural producers during those years. Specifically in this article we tackle a series of aesthetic experiences that can be included within what the Argentinian artist and sociologist Roberto Jacoby called "strategy of joy". According to Jacoby, this strategy "can be described very simply as the attempt to retrieve the mood through actions associated with the music, make them a form of molecular resistance and generate a diffuse, intermittent and own territoriality" (Jacoby, 2000: 16). That strategy arose during the last dictatorship in the rock scene in order to trigger the petrified bodies of young people; during the democratic transition the ?strategy of joy? diversified from a series spaces, festivals, performances, recitals, and samples that shaped a corrosive and irreverent under scene that renewed and vitalize the Buenos Aires cultural field. The hypothesis guiding this study suggests that these aesthetic projects can be understood as a reaction against the attacks by the dictatorship, resistance and confrontation that defied those attacks insolently establishing new ways to create art and (micro)politics through festive, joyful and vital gatherings, where the body played an essential role: as the means through which art was created, as a territory for sexual disobedience, as a canvas, as the means to experience new sensory dimensions, as a way to express-act, as a surface for pleasure, and as a means to be (with others) in the world.